2018
DOI: 10.1002/jbt.22259
|View full text |Cite
|
Sign up to set email alerts
|

Developmental effects of trichloroacetate in Zebrafish embryos: Association with the production of superoxide anion

Abstract: To assess the developmental toxicity of trichloroacetate (TCA), zebrafish embryos were exposed to 8 to 48 mM of TCA and evaluated for developmental milestones from 8‐ to 144‐hour postfertilization (hpf). All developmental toxicities are reported in this paper. Embryos were found to have developed edema in response to 16 to 48 mM of TCA exposure at 32‐ to 80‐hpf, experienced delay in hatching success in response to 24 to 48 mM at 80‐hpf. Lordosis was observed in developing embryos exposed to 40 to 48 mM at 55‐ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The most frequently malformation mentioned in the literature is lordosis [34][35][36][37]. However, the term "lordosis" has also frequently been used as a generic term for any type of curvature of the spine [38]. Another study, however, correctly identified lordosis, but annotated "scoliosis"…”
Section: Sublethal Morphological Alterations In Zebrafish Embryos Witmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently malformation mentioned in the literature is lordosis [34][35][36][37]. However, the term "lordosis" has also frequently been used as a generic term for any type of curvature of the spine [38]. Another study, however, correctly identified lordosis, but annotated "scoliosis"…”
Section: Sublethal Morphological Alterations In Zebrafish Embryos Witmentioning
confidence: 99%
“…Lordosis, for example, is a term frequently used for all types of back curvatures and deformations, whilst these should be divided into lordosis (hyperextension of the back), kyphosis (hunchback) and scoliosis (sideways curvature). Whereas some publications correctly identify lordosis as a hyperextension of the back [34][35][36][37], other communications use this term to describe what was actually scoliosis [38]. One paper correctly determined lordosis, but scoliosis was annotated as "spinal column flexure (tail defect)", and alterations noted as kyphosis rather appear as a break in the spinal column than a curvature [39].…”
Section: Introductionmentioning
confidence: 99%